Efficacy of narrow band UVB with or without OMP in stabilization of vitiligo activity in skin photo‐types (III–V): A double‐blind, randomized, placebo‐controlled, prospective, multicenter study. Issue 3 (18th November 2021) - Esmat, Samia M.; El‐Mofty, Medhat; Rasheed, H.; Mostafa, Wedad Z.; Anbar, Tag S.; Abdallah, Marwa; Bassiouny, Dalia; Abdel‐Halim, Dalia; Hegazy, Rehab; Eid, Amira Abulfotooh; Nassar, Ahmed; Abdel‐Aziz, Rasha TA; et al.
Abstract: Background: NB‐UVB has long been the vitiligo management pillar with capability of achieving the main treatment outcomes; repigmentation and stabilization. Its stabilizing effect in dark skin has been debatable. However, randomized controlled trials regarding NB‐UVB ability to control disease activity are lacking. Purpose: To assess stabilizing effect of NB‐UVB in comparison to systemic corticosteroids, the mainstay in vitiligo stabilization, in skin photo‐types (III‐V). Methods: This is a multicenter, placebo‐controlled, randomized, prospective study. Eighty patients with active nonsegmental vitiligo (NSV) (Vitiligo disease activity (VIDA) ≥2) were randomized to either NB‐UVB and placebo (NB‐placebo) or NB‐UVB and dexamethasone oral mini‐pulse (OMP) therapy (NB‐OMP) for 6 months. Sixty four patients completed the study, 34 in the NB‐OMP group and 30 in the NB‐placebo group. Patients were evaluated fortnightly according to presence or absence of symptoms/signs of activity. Results: In spite of earlier control of disease activity observed in the NB‐OMP group, it was comparable in both groups by the end of the study period. Disease activity prior to therapy, but not extent, was found to influence control of activity in both groups. Thus, NB‐UVB is a safe sole therapeutic tool in vitiligo management. Not only does it efficiently achieve repigmentation, but also it is a comparable stabilizing tool for systemic corticosteroids in spite of slightly delayed control. Conclusion: NB‐UVB is the only well‐established vitiligo therapy that can be used solely whenever corticosteroids are contraindicated or immune‐suppression is unjustified. Nonetheless, its combination with corticosteroids expedites response and improves compliance.